2021
DOI: 10.1021/acsabm.1c01075
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Performance of Zr-BMG, Stainless Steel, and Titanium Alloy with Laser-Induced Periodic Surface Structures

Abstract: A laser-induced periodic surface structure (LIPSS) was shown to have antibacterial adhesion properties in previous research. In this study, the antibacterial performance of LIPSS on traditional biometals (stainless steel and titanium alloy) and a potential biometal (zirconium-based bulk metallic glass, Zr-BMG) was investigated. A femtosecond laser was used to fabricate LIPSS on the specimens. Gram-negative Escherichia coli (E. coli) and Gram-positive Staphylococcus aureus (S. aureus) were used to examine the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Recently, it was shown that the antibacterial performance of metallic glasses can be further improved by surface modifications. Using the femtosecond laser to obtain the nanostructured surface, the antibacterial properties of the ZrCuNiAlTi BMGs were greatly increased, while maintaining cytocompatibility [ 72 , 73 , 118 ]. Further increase was observed due to the Ag deposition with H 2 O 2 treatment [ 73 ].…”
Section: Zr-based Metallic Glassesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that the antibacterial performance of metallic glasses can be further improved by surface modifications. Using the femtosecond laser to obtain the nanostructured surface, the antibacterial properties of the ZrCuNiAlTi BMGs were greatly increased, while maintaining cytocompatibility [ 72 , 73 , 118 ]. Further increase was observed due to the Ag deposition with H 2 O 2 treatment [ 73 ].…”
Section: Zr-based Metallic Glassesmentioning
confidence: 99%
“…The described femtosecond laser surface nanostructuring (see Section 2.4 ) also proved its effectiveness in the in vivo research on BALB/c mice. The implantation of the Zr 43.3 Cu 27.8 Ni 15.2 Al 9.1 Ti 4.6 BMG with a laser-induced periodic surface structure beneath the skin of mice [ 118 ] and attachment to the femur bone [ 73 ] caused no abnormal blood parameters or tissue fibrosis proving the good biocompatibility. The results were obtained even though the intentional application of S. aureus on the implant surface before surgery [ 73 ] showing the exceptional ability of the material to prevent peri-implant infections.…”
Section: Zr-based Metallic Glassesmentioning
confidence: 99%
“…Intriguingly, bacteria on the NP and LIPSS surfaces presented distinctly separated morphologies without aggregation. The LIPSS surfaces exhibited the lowest adhesion force, which could be caused by the lowest adhesion area. ,, This decreased adhesion area was attributed to the large structural intervals of LIPSS, leading to the hill-top adhesion model, which could lift the bacteria to lower the contact area between the material surface and the bacteria (Figure B,C). , …”
Section: Resultsmentioning
confidence: 98%
“…This is also in concordance with reported antimicrobial studies on LIPSS generation on metallic surfaces. 25 The laser modified titanium surfaces supported better cell proliferation compared to stainless steel. Further, the osteogenic potential was unaffected on unpolished surfaces while polished surfaces showed enhanced osteogenic effect upon laser induction (highest for H1P700 modification).…”
Section: Discussionmentioning
confidence: 96%